Collaborative Governance in the Implementation of E-Voting: A Study of District Elections in Sleman Regency - Rizqullah, Abdurrahman Zaki (LP2M INSURI Ponorogo, 2024)
The research is to look at collaboration in the implementation E-voting system in Sleman Regency. The election of Village Heads using an E-voting system is something new for the community. The problem is focused on the collaboration sector between stakeholders in the Village Head Election in Banyuraden District, Sleman Regency. This research aims to see the form of collaboration between the Field Technical Personnel and General Technical Personnel in the implementation of the Village Head Election at Banyuraden Sub Governance theory used as a reference. The research is to use qualitative research methods and descriptive analysis techniques. The instrument used is data collection obtained from the results of Primar and Second data. Primary data was obtained from interviews with Sleman Regency Community and Village Empowerment Service, Field Technical Officers, and general Technical Officers, and Secondary data was obtained from research journals, news, and several written sources that support this research. This study concluded that the collaboration created had an impact on the course of village head elections in Sleman Regency, especially in Banyuraden district.